Analysis of FOXE1 rs4460498 and GSTP-1 I105V associated with non syndromic cleft lip and palate among Deutero Malay Subrace in Indonesia - Nasroen, Saskia Lenggogeni; Meliawaty, Florence; Tammama, Tichvy; Prasdiaz, Putri Indriani; Choirunnisa, Tias; Maskoen, Ani Melani (Universitas Padjadjaran, 2022)
ABSTRACTIntroduction: FOXE1 rs4460498 and GSTP-1 I105V gene polymorphisms are suspected of having a role in some of the non-syndromic cleft lip and palate (NS CLP) populations worldwide. This study aims to analyze FOXE1 rs4460498 and GSTP-1 I105V polymorphisms associated with NS CLP as the risk factor among Deutero Malay Subrace in Indonesia. Methods: This study was a case-control design, using samples from the venous blood of 102 NS CLP subjects and 102 healthy control subjects. After DNA was extracted, the PCR-RFLPs method was performed using TasI restriction enzyme on 100 blood samples of FOXE1 rs4460498 group and Alw26I restriction enzyme on 105 blood samples of the GSTP-1 I105V group. The Chi-Square test was used with the Kolmogorov Smirnov and Exact Fisher alternatives. Results: T mutant allele (OR= 0.926, p>0.05) and CT genotype (OR= 0.0, p>0.05) of FOXE1 rs4460498 and the G mutant allele (OR= 0.988,p>0.05) and AG genotype (OR= 0.675,p>0.05) of the GSTP-1 I105V are not the risks of NS CLP. Conclusion: FOXE1 rs4460498 and GSTP-1 I105V gene polymorphisms are not associated with non-syndromic cleft lip and palate among Deutero Malay Subrace in the Indonesian population.Key words: deutero malay; FOXE1 rs4460498; GSTP-1 I105V; NS CLP